The small RNA diversity from Medicago truncatula roots under biotic interactions evidences the environmental plasticity of the miRNAome - Formey, Damien (2014)
Background: Legume roots show a remarkable plasticity to adapt their architecture to biotic and abiotic constraints, including symbiotic interactions. However, global analysis of miRNA regulation in roots is limited, and a global view of the evolution of miRNA-mediated diversification in different ecotypes is lacking. Results: In the model legume Medicago truncatula, we analyze the small RNA transcriptome of roots submitted to symbiotic and pathogenic interactions. Genome mapping and a computational pipeline identify 416 miRNA candidates, including known and novel variants of 78 miRNA families present in miRBase. Stringent criteria of pre-miRNA prediction yield 52 new mtr-miRNAs, including 27 miRtrons. Analyzing miRNA precursor polymorphisms in 26 M. truncatula ecotypes identifies higher sequence polymorphism in conserved rather than Medicago-specific miRNA precursors. An average of 19 targets, mainly involved in environmental responses and signalling, is predicted per novel miRNA. We identify miRNAs responsive to bacterial and fungal pathogens or symbionts as well as their related Nod and Myc-LCO symbiotic signals. Network analyses reveal modules of new and conserved co-expressed miRNAs that regulate distinct sets of targets, highlighting potential miRNA-regulated biological pathways relevant to pathogenic and symbiotic interactions. Conclusions: We identify 52 novel genuine miRNAs and large plasticity of the root miRNAome in response to the environment, and also in response to purified Myc/Nod signaling molecules. The new miRNAs identified and their sequence variation across M. truncatula ecotypes may be crucial to understand the adaptation of root growth to the soil environment, notably in the agriculturally important legume crops.